JURIDICAL ANALYSIS OF THE HIGH CRIMINAL ACTIONS OF CHILD ABUSE CASES IN THE FRAMEWORK OF IMPLEMENTING JUSTICE IN INDONESIA AS A LEGAL COUNTRY (CASE STUDY IN ANAMBAS ISLANDS DISTRICT) - Syafrudin Semidang Sakti; Fadlan; Erniyanti; Agus Siagian (RADJA PUBLIKA, 2023)
Obscenity is one of the sexual crimes resulting from changes that have occurred in the structure of our society. Sexual abuse is a type of crime that has a very bad impact, especially on the victims, because sexual abuse violates human rights and can damage human dignity, especially the soul, mind and offspring. The victims in these crimes are often children. The increase in criminal acts of sexual abuse committed by children occurred in Anambas Islands Regency in 2020 by 5 cases, then in 2021 there were 6 cases, in 2022 there were 7 cases, and in 2023 there was 1 case. The problems in this research are First; What is the legal regulation of criminal acts of sexual abuse against children in Indonesia?; Second: How is the implementation of the high level of criminal acts of sexual abuse against children in the context of upholding justice in Indonesia as a rule of law (case study in Anambas Islands Regency)?; Third: What factors are obstacles or obstacles and efforts to eradicate the high level of criminal acts of sexual abuse against children in the context of upholding justice in Indonesia as a rule of law? This research uses a descriptive method with normative and sociological research types using a normative approach (legal research) to obtain primary data through field research (research). The research results show that First; The legal regulation of criminal acts of sexual abuse against children in Indonesia is to impose a crime below a special minimum, the judge has deviated from the Child Protection Law which regulates the provisions for minimum sanctions that have been regulated for each special crime; Second; Implementation of the High Crime of Child Abuse Cases in the Context of Upholding Justice in Indonesia as a Rule of Law State (Case Study in Anambas Islands Regency); In accordance with the rules in Article 7 paragraph (2) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. that diversion can only be given to children who have committed a crime with a prison sentence of less than 7 (seven) years and is not a repetition of the crime. Meanwhile, in the case of sexual abuse, perpetrators of criminal acts are subject to imprisonment for a maximum of 15 (fifteen) years, therefore diversion cannot be applied to children who commit criminal acts of sexual abuse. Third: Factors that become Obstacles or Obstacles and Efforts in Eradicating the High Rate of Criminal Offenses Cases of Child Abuse in the Context of Upholding Justice in Indonesia as a State of Law are the presence of factors such as (1) Factors of Legal Rules and Legislation; (2) Factors of Law Enforcement Officials; (3) Supporting Facilities or Facilities Factors; (4) Community Factors; (5) Cultural Factors.